A harmony of Samuel, Kings and Chronicles the books of the Kings of Judah and Israel - Crockett, William Day (Grand Rapids, MI Baker, 1951)
Includes index.
Keywords: Bible. O.T. Samuel -- harmonies; Bible. O.T. Kings -- harmonies; Bible. O.T. Chronicles -- harmonies